FORMATION OF PROFESSIONAL AND PEDAGOGICAL FUTURE TEACHER ORIENTATIONS AS FUNDAMENTALS HIS PEDAGOGICAL CULTURE - R.M. Moiseyenko (Academy of Cognitive and Natural Sciences, 2022)
The author in the article determines the result of research on the problem of professional and pedagogically-oriented forming as basic part of teacher's culture.